A simple greedy algorithm for a class of shuttle transportation problems - Zheng, Yujun; Xu, Chuanqing; Xue, Jinyun (Optimization letters, 2009)
Greedy algorithms for combinatorial optimization problems are typically direct and efficient, but hard to prove optimality. The paper presents a special class of transportation problems where a supplier sends goods to a set of customers, returning to the source after each delivery. We show that these problems with different objective functions share a common structural property, and therefore a simple but powerful generic greedy algorithm yields optimal solutions for all of them.